Finon [Finance for Non Finance] : Manajemen keuangan untuk non keuangan / Said Kelana Asnawi, Chandra Wijaya. - SAID KELANA ASNAWI; Chandra Wijaya (Raja Grafindo Persada, 2015)
xxv, 218 hlm. : ilus. ; 23 cm [ 3 eks.]